Armyanskiy vopros i genotsid armyan v Turtsii : kratkaya bibliografiya literaturı na Russkom Yazıke) = The Armenian question and the genocide of the Armenians in Turkey : a brief bibliography of Russian materials (Los Andjeles = Los Angeles)
177 s.